Effect of do-not-resuscitate orders on patients with sepsis in the medical intensive care unit: a retrospective, observational and propensity score-matched study in a tertiary referral hospital in Taiwan. Issue 6 (16th June 2019) - Chang, Ya-Chun; Fang, Ying-Tang; Chen, Hung-Cheng; Lin, Chiung-Yu; Chang, Yu-Ping; Chen, Yu-Mu; Huang, Chi-Han; Huang, Kuo-Tung; Chang, Huang-Chih; Su, Mao-Chang; Wang, Yi-Hsi; Wang, Chin-Chou; et al.
Abstract : Objective: The aim of this study was to determine whether do-not-resuscitate (DNR) orders affect outcomes in patients with sepsis admitted to intensive care unit (ICU). Design: This is a retrospective observational study. Participants: We enrolled 796 consecutive adult intensive care patients at Kaohsiung Chang Gung Memorial Hospital, a 2700-bed tertiary teaching hospital in southern Taiwan. A total of 717 patients were included. Main measures: Clinical factors such as age, gender and other clinical factors possibly related to DNR orders and hospital mortality were recorded. Key results: There were 455 patients in the group without DNR orders and 262 patients in the group with DNR orders. Within the DNR group, patients were further grouped into early (orders signed on intensive care day 1, n=126) and late (signed after day 1, n=136). Patients in the DNR group were older and more likely to have malignancy than the group without DNR orders. Mortality at days 7, 14 and 28, as well as intensive care and hospital mortality, were all worse in these patients even after propensity-score matching. There were higher Charlson Comorbidity Index in the emergency room, but better outcomes in those with early-DNR orders compared with late-DNR orders. Conclusions: DNR orders may predict worse outcomes for patients with sepsis admitted to medical ICUs. The survival rate in the early-DNR order group was not inferior to the late-DNR order group.